2014
DOI: 10.2320/matertrans.m2013251
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution of AZ80 Magnesium Alloy during Multi-Directional Forging Process

Abstract: Grain refinement of a magnesium alloy, AZ80, was studied in multi-directional forging (MDF) with decreasing temperatures from 683 to 573 K. The MDF was carried out up to accumulative true strains of around 7 with changing the loading direction from pass to pass. The structural changes are characterized by the alternate appearance of fine dynamic recrystallized (DRXed) grains (with many dynamic granular Mg 17 Al 12 phases) and coarse DRXed grains (without Mg 17 Al 12 phases) in the sample, the expansion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, most investigations of MDF have 3 concentrated on using this procedure to process aluminum alloys [18] and ferroalloys [19]. However, only a few studies have been reported on MDF of magnesium alloys [20][21][22][23]. Our previous work has investigated the microstructure and mechanical properties of micron-SiCp/AZ91 magnesium matrix composite processed by MDF [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, most investigations of MDF have 3 concentrated on using this procedure to process aluminum alloys [18] and ferroalloys [19]. However, only a few studies have been reported on MDF of magnesium alloys [20][21][22][23]. Our previous work has investigated the microstructure and mechanical properties of micron-SiCp/AZ91 magnesium matrix composite processed by MDF [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…With the accumulation of strain, the orientation of the grains turns in the direction that is most favorable to the slip and the twins disappear (shown in Figure 6c,d). Furthermore, the distortion energy stored by twinning and the activation of non-basal slip are responsible for the nucleation of dynamic recrystallization (DRX) [27]. In addition, Figure 6a,b reveal that the "necklace" structure is full of matrix, indicating that DRX occurs and the grain begins to refine [28].…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…equal channel angular pressing (ECAP), high-pressure torsion (HPT), multidirectional forging (MDF) and accumulative roll-bonding (ARB) etc., are now available, MDF seems to be especially attractive for its potential for scaling up of relatively large samples that can be suitable for industrial applications [18,19]. So far, most investigations of MDF have concentrated on using this procedure to process pure metals or metallic alloys [20][21][22][23][24][25][26]. Our previous work has investigated the microstructure and mechanical properties of micron-SiCp/AZ91 magnesium matrix composite processed by MDF [27,28].…”
Section: Introductionmentioning
confidence: 99%